Quantitative Analysis of Thin Section using Frequency Measurement (Point Counting), a Case Study on Limestone of The Rajamandala Formation, Cikamuning, West Java, Indonesia - Khorniawan, Wahyu Budhi; Ringga Jayanti, Anita Galih; Caesario, Dipo (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The description of thin sections observations has traditionally relied on the visual comparison method, often using a visual comparison chart. However, this method has interpretative limitations, as readings can vary between individuals, and the values produced tend to be rounded. The point counting method for determining frequency is one of the statistical approaches that quantitatively counts the presence of mineral grains or particles. The limestone samples were collected from the Rajamandala Formation in the Cikamuning area of West Java, Indonesia. The methodology involved petrographic observations using the point counting method, which entailed creating a grid on the thin sections with a total of 312 points and calculating the percentage of occurrence of the constituent rock compositions. The analysis results showed constituent composition percentages of 33.65% for corals, 52.24% for matrix, 4.81% for cement, 2.56% for calcite, 3.85% for replacement, and 2.88% for porosity, categorizing the rock as coral wackstone. The facies is determined based on the presence of biota, while diagenesis is determined by the presence of cement types, secondary porosity, and grain contacts. In the research area, the identified facies is open marine (FZ 7), and the diagenesis includes marine phreatic, meteoric phreatic, and burial diagenesis.